Right to Life in the American Medical System - Cavanagh, Denis (Medicina e Morale, 1996)
The article deals with the impact of the so called "culture of death" on medical practice in United States (US). In fact, in America, while the pretence is being kept up on the importance of the Hippocratic oath and the evangelic benevolence of the Good Samaritan, the strategy of the secular humanists is to try to make these irrelevant in the twin interests of social convenience and fiscal security. This campaign has been quietly waged in the media, in the courts, in public schools and universities. According this strategy, the threats to human life are, namely, two: abortion and euthanasia. On the first issue, in US the situation is discouraging because the US Supreme Court rulings Roe v. Wade and Doe v. Bolton in 1973, that have made abortion a woman's choice for any reason in the first and second trimester and available with medical consultation for almost any reason in the third trimester of pregnancy. Regarding the euthanasia, the campaign strategy is following the same pattern as that used to legalize abortion: the Euthanasia Lobby is claiming that millions of people in America are suffering unbearable pain because of terminal illness and so ought to have the right to end their pain with physician- assisted suicide. On the contrary, the author assert that there is no right to destroy any human life or participate in its destruction and there is no good moral reason for abortion or euthanasia, including the physician-assisted suicide. Finally, the author think that it is vital that Catholic activists, allied with Christian church-going brethren, should resist with all the power they can muster to the "culture of death".